A Standardized Chinese Herbal Decoction, Kai-Xin-San, Restores Decreased Levels of Neurotransmitters and Neurotrophic Factors in the Brain of Chronic Stress-Induced Depressive Rats. (29th August 2012) - Zhu, Kevin Yue; Mao, Qing-Qiu; Ip, Siu-Po; Choi, Roy Chi-Yan; Dong, Tina Ting-Xia; Lau, David Tai-Wai; Tsim, Karl Wah-Keung
Abstract : Kai-xin-san (KXS), a Chinese herbal decoction being prescribed by Sun Simiao in Beiji Qianjin Yaofang about 1400 years ago, contains Ginseng Radix et Rhizoma, Polygalae Radix, Acori tatarinowii Rhizoma, and Poria. KXS has been used to treat stress-related psychiatric disease with the symptoms of depression and forgetfulness in ancient China until today. However, the mechanism of its antidepression action is still unknown. Here, the chronic mild-stress-(CMS-) induced depressive rats were applied in exploring the action mechanisms of KXS treatment. Daily intragastric administration of KXS for four weeks significantly alleviated the CMS-induced depressive symptoms displayed by enhanced sucrose consumption. In addition, the expressions of those molecular bio-markers relating to depression in rat brains were altered by the treatment of KXS. These KXS-regulated brain biomarkers included: (i) the levels of dopamine, norepinephrine, and serotonin (ii) the transcript levels of proteins relating to neurotransmitter metabolism; (iii) the transcript levels of neurotrophic factors and their receptors. The results suggested that the anti-depressant-like action of KXS might be mediated by an increase of neurotransmitters and expression of neurotrophic factors and its corresponding receptors in the brain. Thus, KXS could serve as alternative medicine, or health food supplement, for patients suffering from depression.